DEVELOPMENT AND CHARACTERIZATION OF POLYCLONAL ANTIBODY OF RECOMBINANT HUMAN INTERFERON Α2B IN NEW ZEALAND WHITE RABBIT - Heni Rachmawati (Indonesian Journal of Pharmacy, 2014)
We have developed recombinant wild type and mutant human interferon α2b (rhIFNα2b) from synthetic gene in Escherichia coli. To identify the successful product of the proteins, immunology-based assay was suggested due to specificity for characterization. This work was aimed to develop and characterize rhIFNα2b polyclonal antibody generated in White New Zealand rabbits. The rhIFNα2b was overproduced in Escherichia coli BL21 containing rhIFNα2b synthetic gene in pET32b.The protein was obtained as inclusion bodies, refolded, purified using nickel affinity chromatography, and characterized using polyacrylamide gel electrophoresis. The purified rhIFNα2b protein was injected into rabbits for 21 days. Absorption of E.coli antibody was done using total E. coli protein to remove antibody againts host cell.   The generation of antibody was monitored using dot blot and Western blot methods and quantified using Enzyme Linked Immunsorbant Assay (ELISA). To do so, rhIFNa2b was used as an antigen. The result showed that the rhIFNα2b was produced as a His-tag protein fusion of 33kDa in size. The results of dot blot and Western blot analyses strongly indicated that antibody against rhIFNα2b was generated and specifically recognized rhIFNα2b. ELISA showed that the titer of the polyclonal anti-rhIFNα2b was 1:10.000. In conclusion, polyclonal antibody spesifically against rhIFNα2b protein was successfully detected with high titer after 21 days after rabbit immunization.